Reporting quality of abstracts of trials published in top five pain journals: A protocol for a systematic survey - Sriganesh, Kamath; Bharadwaj, Suparna; Wang, Mei; Abbade, Luciana P. F. [UNESP]; Couban, Rachel; Mbuagbaw, Lawrence; Thabane, Lehana (BMJ, 2016)
Introduction: Abstracts of randomised controlled trials (RCTs) are often the first and the only source read in a journal by busy healthcare providers. This necessitates good reporting of abstracts. The quality of reporting of abstracts, though gradually improving over time, is still not uniform across medical journals. Improvement in completeness of reporting of abstracts has been documented in general medical journals after the publication of the consolidated standards of reporting trials (CONSORT) extension for abstracts in 2008. Currently, this aspect has not been assessed with regards to pain journals. This study aims to compare the completeness of reporting of abstracts before and after the publication of CONSORT statement for abstracts in five pain journals. Methods and analyses: The abstracts of RCTs published from 1 January 2005 to 31 December 2007 (pre-CONSORT) and from 1 January 2013 to 31 December 2015 (post-CONSORT) will be assessed for the quality of reporting. Studies without abstracts, non-English abstracts, abstracts not reporting on RCTs or on humans and conference abstracts will be excluded. A thorough search of MEDLINE will be carried out in April 2016. All identified studies will be screened for inclusion based on titles and abstracts. Data will be extracted by two sets of independent reviewers for each abstract in duplicate regarding compliance with CONSORT statement for abstracts. Full-text review will be performed to obtain additional characteristics which are likely to affect reporting quality. The unadjusted and adjusted differences in the mean number of items reported will be analysed using a two sample t-test and generalised estimation equation in SPSS. Ethics and dissemination: As far as we know, this is the first study to evaluate reporting quality of abstracts of pain journals based on CONSORT extension for abstracts. The findings of this study will be disseminated by a presentation at a conference and through publication in a peer-reviewed journal. Ethics committee approval was not sought for this survey.
Keywords: PAIN MANAGEMENT; QUALITATIVE RESEARCH